Pedagogical dilemmas among Bedouin-Palestinian peace educators in Israel. Issue 3 (12th August 2019) - Litvak Hirsch, Tal; Lazar, Alon; Abu Hadubah, Kamal
Abstract : Purpose: The purpose of this study is to learn how minority peace educators grapple with dilemmas related to their involvement in peace programs. Design/methodology/approach: A total of 15 male teachers, members of the minority Bedouin community in Israel, all peace educators, provided their reactions to three dilemmas, addressing various facets of the strained relations of their community with the Jewish-Israeli majority, as influenced by the Israeli–Palestinian conflict. Findings: The responses to these dilemmas suggest that when it comes to questions of the identity of these teachers as members of a marginalized community, their responses considerably diverge. This is not the case when it comes to their identity as peace educators. Originality/value: This suggests that if the aim is to bring peace educators, members of minority groups in conflict zones, to harness their potential to bring about positive change, their peace activist identities must be strengthened.